2015
DOI: 10.1177/0023677215597137
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effect of storage conditions on prothrombin time, activated partial thromboplastin time and fibrinogen concentration in rat plasma samples

Abstract: Coagulation parameters are usually included in clinical and preclinical safety studies to evaluate the effect of xenobiotics on the extrinsic or intrinsic pathways of coagulation. The analysis is generally performed at the time of terminal sacrifice where many activities are scheduled. Chances of delay in analysis are likely particularly when blood is collected for coagulation via the abdominal vena cava. This experiment was planned to assess the variations in coagulation parameters caused by delay in analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Our finding is also at variance with a previous report which indicated that prothrombin time and APTT results are stable for up to 24 h and 8 h respectively, remaining constant regardless of storage conditions [10]. Also, Goyal and colleagues [11] evaluated coagulation parameters (PT and APTT) at 0, 6, 24 and 48 h from the plasma stored at room temperature, as well as plasma stored under refrigerated and freezing conditions and observed that PT can be stored and analysed without any significant changes for up to 6 h from the actual blood collection, while for APTT results, plasma samples should be run immediately after collection. Our finding is consistent with previous report [12] which reported that PT and APTT can be reliably tested after storage for 8 h at room temperature and that the acceptable time interval can easily be extended to 24 h for PT determination.…”
Section: Discussioncontrasting
confidence: 50%
“…Our finding is also at variance with a previous report which indicated that prothrombin time and APTT results are stable for up to 24 h and 8 h respectively, remaining constant regardless of storage conditions [10]. Also, Goyal and colleagues [11] evaluated coagulation parameters (PT and APTT) at 0, 6, 24 and 48 h from the plasma stored at room temperature, as well as plasma stored under refrigerated and freezing conditions and observed that PT can be stored and analysed without any significant changes for up to 6 h from the actual blood collection, while for APTT results, plasma samples should be run immediately after collection. Our finding is consistent with previous report [12] which reported that PT and APTT can be reliably tested after storage for 8 h at room temperature and that the acceptable time interval can easily be extended to 24 h for PT determination.…”
Section: Discussioncontrasting
confidence: 50%
“…For rat blood samples, plasma should be run immediately after collection for reliable activated partial thromboplastin time results [3]. For dog blood samples, differences in white blood cell (WBC) and platelet (PLT) counts varied with the specimen [4].…”
mentioning
confidence: 99%
“…Prothrombin time and Ptt were measured according to the method described by Goyal et al (2015) using a CoaDATA automated analyzer (Ahrensburg, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%